DIGITAL TOOLS FOR MATCHING QUALIFICATIONS TO THE LEVELS OF THE NATIONAL QUALIFICATIONS FRAMEWORK - Volodymyr Kovtunets; Sergiy Londar; Serhii Melnyk; Oles Kovtunets (Інформаційні технології і засоби навчання)
Mutual compatibility of different national qualifications frameworks (NQFs) based on their compatibility with the European Qualifications Framework (or another international one) is crucially important for the effective recognition of qualifications between states. In turn, it depends on the quality of “filling” NQF levels with qualifications. Right comparing professional (occupational) qualifications with  NQF level is a non-trivial problem for standard developers. The quality of any national system of qualifications depends on the comparability of qualifications with the level of the NQF so the comparison process should be strongly argued to secure the comparability. For qualification standard developers (especially for occupational standard developers) there were no strictly justified recommendations on how to compare qualification with the NQF level. Th. Saaty’s Analytic Hierarchy Process (AHP) is developed to resolve the problem of evidence-based comparing educational or professional (occupational) qualifications with the level of the National Qualification Framework (NQF). Research results give standard developers software tools based on a strong mathematical background to determine NQF level for developed standards. It is shown that Th. Saaty’s Analytic Hierarchy Process (AHP) is close to optimal for solving the problem of qualifications comparing and therefore looks like the best option for such methods. However, AHP demands non-trivial qualifications in mathematics and computing. The key problem resolved by this research is simplifying procedures to ensure effective access to the tool for qualification standard developers with minimal qualification in mathematics and computing. It is proven that each problem of qualification comparison with NQF level may be reduced to three options of decision. At the lower level of the decision-making process, there are 3-4 descriptors of qualification. Therefore, a user should be capable of forming at most four matrices of judgments and computing the main eigenvectors with some level of accuracy. The maximal dimension of matrices is four (for example it's true for the Ukrainian case). But for some national qualification frameworks that use only three descriptors maximal dimension of matrices equals three. Therefore, some simple approximation methods for eigenvector computing may be applied using only minimal means of Microsoft Excel or analogous applications. For the most general case of four NQF descriptors, Microsoft Excel macro is developed to secure achieving any level of accuracy. Corresponding API is developed by PHP programming language. Both Excel and API are accessible for users at the website of the Institute of Educational Analytics in Kyiv. The novelty of the article is that for the first time in national and international practice, it proposes an alternative/supplementary algorithmic method for determining the level of certain full and/or partial professional qualifications by the National Qualifications Framework, thus creating prerequisites for further automation of the activities of professional standards developers.